MENINGKATKAN KUALITAS KARYA ILMIAH MAHASISWA MELALUI BIMBINGAN SELF REGULATED LEARNING - Latipah, Eva (QUALITY, 2017)
This study was conducted to design a guidance model of self regulated learning and test effectiveness of this model in improving quality of students scientific work. Design of model is done by identifying needs of students and apply model in guidance process of students scientific work. Subjects in this study are student who is writing their thesis numbered 42 people in UIN Sunan KAlijaga Yogyakarta. The results show that students need guidance on a strategy to complete thesis quickly and precisely. By applying that guidance model quality of students thesis  increased significantly shown in value of thesis that be obtained.